Beriman Personal Sekaligus Komunal: Refleksi Kritis Beriman untuk Zaman Sekarang - Yohanes Anggi Witono Hadi (P3TK, Sanata Dharma University, 2019)
Faith is a total surrender to God. Faith also means believing in God who nourishes for human life. Trust in God is a form of personal faith between humans and God. But it's not enough if we just have personal faith, because humans were called to believe communally too. Personal and communal faith means manifesting and celebrating our faith in real situations.Faith in the Church and society is a holy and living communion. Personal and communal faith is a form of faith that is in accordance with the essence of the Catholic Church.